Critical slope lenght and water erosion, in three rates of crop residue and two modes of direct seeding - Amaral, André Julio do; Cogo, Neroli Pedro; Bertol, Ildegardis (Revista de Ciências Agroveterinárias, 2014)
The objective of this work was to investigate the existence of critical slope lengths, associated with corn residue failure, at the rates of 8, 4, and, 2 Mg ha-1, in two modes of direct seeding: without and with shanks grooving in the seeding-fertilizing machine. Simulated rainfall of 75 mm h-1, applied with the rotating-boom simulator, and an Alfisol with 0.16 m m-1 slope steepness, were used. Initially only applied rain was used, until steady runoff occured. Increasingly, without interrupting and changing the intensity of the rain, increasing levels of extra-water inflow (six, 10 minutes each) were added to the experimental plots, to simulate progressively greater slope lengths. There was effective residue removal by surface runoff in all treatments, which led to believe the same failure or critical slope length existed in all of them, but this could not be confirmed by the theoretical erosion relationships. Even so, as a reference and as a measure of safety, real credit was given to what was visually observed, a failure in smaller residue level of extra flow in direct seeding without chisel planter was observed, and the opposite with the chisel planter, establishing critical slope lengths, respectively, of 64 m to 118 m and 171 m to 456 m, according to residue rates.